2012
DOI: 10.1111/j.1537-2995.2012.03775.x
|View full text |Cite
|
Sign up to set email alerts
|

Stored platelets alter glycerophospholipid and sphingolipid species, which are differentially transferred to newly released extracellular vesicles

Abstract: BACKGROUND: Stored platelet concentrates (PLCs) for transfusion develop a platelet storage lesion (PSL), resulting in decreased platelet (PLT) viability and function. The processes leading to PSL have not been described in detail and no data describe molecular changes occurring in all three components of stored PLCs: PLTs, PLC extracellular vesicles (PLC‐EVs), and plasma. STUDY DESIGN AND METHODS: Fifty PLCs from healthy individuals were stored under standard blood banking conditions for 5 days. Changes in cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 71 publications
(84 reference statements)
5
55
0
Order By: Relevance
“…Lipid extraction from PL‐EVs (corresponding to 100 μg of total protein), lipid processing, and quantification by lipid mass spectrometry of cholesterol, glycerophospholipids, and major sphingolipids were carried out as earlier (http://onlinelibrary.wiley.com/doi/10.1111/trf.12874/suppinfo). Minor sphingolipids and glycerophospholipids including cardiolipin (CL) and bis(monoacylglycero)phosphate were analyzed by hydrophilic interaction according to Scherer and colleagues .…”
Section: Methodsmentioning
confidence: 99%
“…Lipid extraction from PL‐EVs (corresponding to 100 μg of total protein), lipid processing, and quantification by lipid mass spectrometry of cholesterol, glycerophospholipids, and major sphingolipids were carried out as earlier (http://onlinelibrary.wiley.com/doi/10.1111/trf.12874/suppinfo). Minor sphingolipids and glycerophospholipids including cardiolipin (CL) and bis(monoacylglycero)phosphate were analyzed by hydrophilic interaction according to Scherer and colleagues .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to this, human plasma contains S1P and also dihydrosphingosine, but little ceramide 25 . Separately, stored platelets were found to transfer phospholipids and sphingolipids to newly released extracellular vesicles resulting in increased ceramide and decreased S1P in the cells 28 .…”
Section: Specific Lipid Families In Plateletsmentioning
confidence: 99%
“…Using traditional methods, individual lipid pools first had to be isolated using TLC, then hydrolyzed to release FAs for determination as free acid species, a considerably slower approach that requires more material 1-4 . Recently, the composition of stored platelets and extracellular vesicles were characterized, showing that vesicles became enriched with LPA, cholesterol, and other lipids 28, 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of S1P in human platelets decreases upon storage, which is associated with elevation in ceramide level ( 31 ). It was shown that thrombocytes are able to dephosphorylate S1P (most likely with the help of LPP) and incorporate released sphingosine into ceramide and then sphingomyelin via the action of ceramide synthase and sphingomyelin synthase ( 25,28 ).…”
mentioning
confidence: 99%